Retrospective analysis of fosfomycin combinational therapy for sepsis caused by carbapenem-resistant Klebsiella pneumoniae - Liao, Yun (Exp Ther Med, 2017)
The aim of the present study was to compare the efficacy and safety of fosfomycin combinational therapy with other antibiotics for the treatment of infections caused by carbapenem-resistant Klebsiella pneumoniae (CRKP). This retrospective cohort study examined 104 cases of sepsis caused by CRKP occurring between January 2012 and November 2014 in Shanghai Tenth People's Hospital. Three categories of patient outcome were assessed: Survival/mortality, duration of intensive care unit stays and duration of medical ventilation. Univariate ordinal analyses were adopted to evaluate the correlations between outcome and treatment. A total of 104 patients with physician-diagnosed CRKP were involved in the study. The overall mortality rate was 25.0%. The majority of the infections (84; 80.8%) were hospital acquired. Critical infections received more than one active antibiotic as therapy. Patients treated with fosfomycin combinational therapy were less likely to fail therapy (OR: 4.71, 95% CI: 1.03–21.65, P=0.034) and tended to have a shorter duration of mechanical ventilation. Gender (OR: 4.35, 95% CI: 1.08–3.60, P=0.037), history of chronic obstructive pulmonary disease (OR: 9.35, 95% CI: 0.06–0.19, P=0.007) and peripheral catheter use (OR: 3.00, 95% CI: 0.07–0.19, P=0.002) are risk factors for clinical outcome. Therefore, the use of fosfomycin combinational therapy for treatment of infection due to CRKP appears to be associated with improved survival rate.